Матеріали з досліджень О. Г. Шапошникової та Д. Я. Телегіна у Старобільському районі Луганщини - Теліженко, С.А. (Археологія і давня історія України, 2020)
У публікації проаналізовано маловідомі матеріали, виявлені в результаті проведення археологічних
досліджень під керівництвом О. Г. Шапошникової
та Д. Я. Телегіна на Луганщині у 1980 та 1985 рр. In 2016 during the inventory and transportation of
the archaeological finds from temporary archaeological
storage at Pheophania to the present-day storage
facility of the Institute of Archaeology, the materials
of the excavations of the expeditions of 1980 and 1985
were selected and processed. The excavations and surveys
were conducted by expeditions under the lead of
O. G. Shaposhnikova and D. Ya. Telehin on the territory
of the Starobilsk district of the Luhansk region.
The surveys in 1980 were conducted at only two locations
located close to each other — the settlements of
Aidar-Bila and Pidhorivka.